PELUANG DAN TANTANGAN DIGITALISASI DALAM INDUSTRI ASURANSI - Arifin, Saiful; Chyntia Hutagalung; Diana RW Napitupulu (Honeste Vivere, 2025)
The insurance industry is undergoing a massive transformation with rapid technological advancements. Future trends in this industry will be heavily influenced by digitalization, insurtech, and the use of Big Data. These innovations create new, very promising opportunities for insurance companies and young professionals who want to build a career in this industry. This study aims to foster a deeper understanding of the opportunities and challenges of digitalization in the Insurance industry trends and progress in related literature, allowing the identification of prospects and obstacles faced by the insurance industry in facing digital transformation, and formulating appropriate strategies to face this increasingly digital future. The systematic literature review (SLR) method, also known as a systematic literature review, is a method that identifies, examines, evaluates, and interprets every available research. Based on the results of the study, it was found that Insurtech has great potential to transform the insurance industry in Indonesia. Regarding the potential of Insurtech in the digital era, it has quite broad future opportunities, because this insurance focuses more on individual or family financial management or even companies. Although challenges will always be there, the insurance industry must remain ready to innovate and we continue to learn to gain a strong competitive advantage in this ever-growing insurance industry.